Analisis Yuridis Putusan KPPU Nomor 08/KPPU-I/2020 Terhadap Dugaan Praktik Diskriminasi Berdasarkan Hukum Persaingan Usaha - Chintia Rizki Hasbi; Hirsanuddin Hirsanuddin (Bagian Hukum Bisnis Fakultas Hukum Universitas Mataram, 2023)
The purpose of this research is to find out the fulfillment of the elements of discrimination in a business competition. The type of legal approaches and legal considerations decided by KPPU in KPPU Decision Number 08/KPPU-I/2020 concerning alleged violations of Article 19 letter d Law Number 5 of 1999. The research method uses normative legal research with a statutory approach, conceptual approach, and a case approach. From the results of the study and analysis, it can be concluded that PT Telekomunikasi Indonesia (Persero) Tbk and PT Telekomunikasi Seluler have been proven to practice discriminatory practices by blocking internet access services for Netflix, in examining this case, KPPU uses the Rule of Reason approach, and the decisions issued by KPPU have not provided a sense of justice to one of the parties, namely Netflix.